Pathology of Spirorchiidae (Digenea: Schistosomatoidea) infection in green turtles(Chelonia mydas) on Campos Basin, Rio de Janeiro - Reina I.A. Cartagena; Joana M.P. Ikeda; Isabela M. Neto; Gabriela O. Pereira; Asheley H.B. Pereira; Raquel O. Simões; José L. Luque; Daniel G. Ubiali (Pesquisa Veterinária Brasileira, 2023)
ABSTRACT: Spirorchidiasis is one of the most common diseases in green turtles. Eggs and the adult form of trematodes are mainly found in the heart, liver, lung, spleen, and gastrointestinal tract. The present study aimed to describe the pathological aspects of Spirorchiidae trematode infection in green turtles (Chelonia mydas) in the Campos Basin, Rio de Janeiro. The current study was based on the necropsy of 99 green turtles (Chelonia mydas, Chelonidae) from April to December 2021. Epidemiological data were obtained from the Aquatic Biota Monitoring Information System (SIMBA). A histopathological examination was performed at the “Setor de Anatomia Patológica” (SAP) from “Universidade Federal Rural do Rio de Janeiro” (UFRuralRJ). Tissue fragments (buccal papilla, esophagus, trachea, lung, heart, kidney, bladder, stomach, liver, spleen, intestines, gonads, adrenal, thyroid, pancreas, salt glands, muscle, and skin) were sampled for histological examination. The green turtles had lesions compatible with parasitic infection in 89% (88/99) cases. Out of 88 turtles, 87 were juveniles (99%), 75% (66/88) were females, and 25% (22/88) were males. Adult parasites and their eggs were found to cause granulomatous tissue reactions in 14% (12/88) of turtles. Egg-associated granulomatous inflammation was found in 86% (76/88) of the turtles. The organs with the highest number of egg-associated granulomas in order of occurrence were: the spleen, small intestine, adrenal gland, pancreas, and lungs. The adult trematodes were observed in histological lesions in order of occurrence, mainly in the esophagus, stomach, and small intestine. Out of the total number of turtles parasitized, 33% (29/88) of deaths occurred due to multiple causes such as fractures, interaction with fishing, predation, and fibropapillomas. The other 67% (59/88) presented multisystemic granulomatous disease caused by Spirorchiidae infection as a cause of death. Evidence is presented that spirorchidiasis is highly prevalent in young green turtles, is responsible for extensive chronic lesions, and responsible for significant debilitation and mortality.